Determinación de la actividad antioxidante de especies medicinales de la provincia de Loja y Zamora Chinchipe - Cuenca Alvarado, Marco Vinicio (2015)
Antioxidants are molecules capable to slow or prevent the oxidation of other different molecules, having many health benefits. In this study, I evaluated the antioxidant activity and the total phenolic content of 73 extracts and 3 secondary metabolites of 40 medicinal plant species from the province of Loja and Zamora Chinchipe. The technic used was Radical DPPH (2,2-diphenyl 1-picrihidracilo) and ABTS 2,2 azinobis (3-ethylbenzthiazoline-6-sulfonic acid); and the total phenol content was measured by the method of Folin-Ciocalteu. In the quantification Trolox and Gallic Acid activity were used as reference standards for antioxidant and content of total phenols. The species analyzed demonstrated to possess a high antioxidant effect according to their IC50 and the total of phenols were: Hypericum lancioide (Dichloromethane), Piper pseudochurumayo (Methanol), Ludwigia peruviana (Methanol), Sarcohachis sydowil Trel (Methanol-Water), Garcinia macrophylla (Methanol ), Clusia alata (Methanol), Huperzia crassa (alkaloid extract), Fuchsia sp. (methanol-water), and the secondary metabolite Tricine. The results indicated a high activity in the methanolic extract and methanol-water; however, hexane extracts presented a very low phenol content and antioxidant activity